Mathematical modeling of logistic systems of industrial enterprises with discount accounting - Слесаренко, Анатолий Павлович; Несторенко, Александр Васильевич (Technology audit and production reserves, 2014)
It is investigated the reasons for the low efficiency of warehouse logistics models taking into account discounts and analyzed their construction. In determining the form of the function of the general costs in models with discounts not taken into account that the cost of shipping and storage, as well as the amount of money spent on the purchase belong to different moments in time. The combination of these observations is one of the main factors affecting the adequacy of mathematical models for inventory management, taking into account the discounts. Analysis of mathematical model, based on the principle of bringing one point in time incoming and outgoing cash flows, showed the possibility of significant differences in decision-making, based on the use of this and classical models. It is developed the algorithm for determining the optimal batch size of delivery with accounting of discounts and optimal number of vehicles to deliver it, which will create an effective information system of logistics.